Occupational injuries in the mining sector (2000-2010). comparison with the construction sector (2014)
This paper compares the incidence of fatal and non-fatal occupational injuries of workers in the mining and construction sectors in Spain between 2000 and 2010. Data on work injuries were obtained from the Spanish Ministry of Labour and Immigration and the denominators were obtained from the available statistics on Social Security registration. We calculated the incidence of fatal and nonfatal occupational injuries, the relative risk (RR) and odds ratio (OR) for a 95% of confidence interval (CI) for the mining workers compared to the construction workers. The obtained results indicate that mining workers have a higher risk of occupational injuries and lost more working days than the construction workers.